Service Quality Bus Rapid Transit Mamminasata Kota Makassar - Shinta Dewi Sugiharti Tikson; Syamsinar Syamsinar; Atika Atika; Indri Leighton Silambi (Journal of Management and Business Review, 2021)
People's interest in using the Mamminasata Bus Rapid Transit (BRT) has decreased significantly. This problem has an impact on the decline in Perum Damri's income. The purpose of this study is to determine the service quality of Mamminasata Bus Rapid Transit in Makassar so that it can increase public interest in using this mode of public transportation. Results show that the maximum gap in this study is -1.49, which means there is a gap between respondents' perceptions and expectations regarding the operational hours of Mamminasata Bus Rapid Transit. Most respondents, as many as 64 people (68.1%), said they did not know the BRT operational hours and the bus often come late to the bus stop. Respondents expectation that the BRT operational hours (arrival and departure) would be timely and clear. The smaller the gap (gap close to zero or positive) the better the service quality of the company. Conversely, the larger the gap, the lower the service quality of a company. Thus, service companies such as Perum Damri which is a provider of the Mamminasata Bus Rapid Transit in Makassar need to prioritize in improving service quality based on the results of the largest gap